GP75 Case of a lifetime – how mosaicism may mislead. (June 2019) - Sasaki, Erina; McArdle, Linda; Adamson, Zephra; Hegarty, Ann Marie; Carty, Paula; Betts, David; Reardon, William
Abstract : A patient was referred in consequence of an abnormal microarray finding. The background history was of Left Congenital Diaphragmatic hernia, coarctation of Aorta and PDA. Examined at 5 weeks by Consultant Clinical Geneticist, she was non-dysmorphic, her head circumference was on 25 th percentile. Neurological examination was age appropriate. ACGH showed a mosaic chromosomal imbalance involving chromosome 2q in the form of a ∼46.7Mb gain of 2q26.1–q31.2 and a ∼17.6Mb loss of 2q36.2–qter, which was estimated to be present in approximate 50% of cells. In contrast G-band karyotype analysis of phytohaemoglutinin stimulated and cultured cells showed no evidence of the abnormal cell line, with only apparently normal female 46, XX metaphases seen. So, there was a data mismatch. Parental karyotypes were both normal. Due to the peripheral blood karyotype result a skin biopsy was taken for culture and karyotyping, together with a buccal smear for FISH analysis. In addition, a second peripheral blood sample was taken to allow FISH analysis on non-cultured cells. These FISH analyses indicated the presence of an abnormal cell line in 19% (buccal smear) and 35% (whole blood) of the 200 cells analysed. Conversely cultured fibroblasts only resulted in cells with a normal female karyotype. Hence, these results indicate that the level of mosaicism varies dramatically between different cell lineages. The absence of the abnormal cell line in the cultured cells would support that this cell line is not present in the T-lymphocytes. A FBC and film showed normal white cell counts and morphology. The findings with the cultured fibroblasts may be reflective of either the absence or scarcity of the abnormal cell line in the biopsy. This most unusual case illustrates that the understanding of how test results are generated and potential limitations of each test is crucial when considering the clinical features of the patient. Further it demonstrates how mosaicism may be unequally distributed between cell types or indeed absent in the actual cell type that is being tested. It is reassuring that the patient is neurologically age appropriate. The management with clinical and developmental observation are warranted to monitor her progress.